Factors driving unified communications and collaboration adoption and use in organizations. Issue 1 (21st March 2016) - Silic, Mario; Back, Andrea
Abstract : Purpose: The purpose of this paper is to reveal factors that drive the adoption and use of unified communications and collaboration (UC&C) technology in organizations. Design/methodology/approach: The authors used quantitative method to survey 296 employees from 50 different countries by conducting and international study. Partial least squares -method was used for the latent variables latent variable analysis Findings: The authors found that unified theory of acceptance and use of technology constructs are mainly validated where results suggests that performance expectancy and social influence are the most influential drivers in employee acceptance and use of UC&C in organizations. Social presence, influence of peers and superiors are the main factors to take into consideration when implementation UC&C technology. Research limitations/implications: The study was not longitudinal in design, which should be addressed by a future study that includes multi-cultural dimensions with a longitudinal design Practical implications: Awareness through education and training of employees needs to be given very particular attention in the future mobile implementations. Moreover, management and employee support is the critical component of the effective information security governance framework implementation. Finally, mobile strategy needs to go over very precise and detailed planning process to ensure the right technology acceptance by users. Originality/value: The authors close the existing research gap by providing useful insights into organizations regarding their UC&C technology adoption and use factors